INCREASING ASEAN ECONOMIC GROWTH THROUGH THE DIGITAL ECONOMY AS AN INITIATIVE IN THE ASEAN INDONESIA CHAIRMANSHIP 2023 - Ari Wibowo (Proceeding International Seminar of Islamic Studies, 2023)
The ASEAN Indonesia Chairmanship 2023 will observe a lot of opportunities and challenges for the bloc in the area of economy. This chairmanship will gear toward strengthening ASEAN’s institutional capacity and increasing its resilience towards challenges. The ASEAN economic growth as well as the digital economy are challenging since its determinants can be analyzed from different points of view in all ASEAN members. This study attempts to explain how ASEAN economic growth relates to digital economy as an initiative in the ASEAN Indonesia Chairmanship 2023. The study uses qualitative research methods as well as empirical research methods with descriptive analysis techniques. The main finding of this research is the growth of Southeast Asia can be attributed to many, however, one of the largely stands out amongst the rest is its rise in the digital economy. There has been a rapid change in digitalization across the 670 million people it holds. The digital economy alone is set to generate over 1 trillion US Dollars by 2025 which is around a quarter of the entire Southeast Asia’s gross domestic product. E-commerce, E-banking, and E-education have all been rapidly accelerated and have named ASEAN as the world’s fastest-growing internet market.